A modified Grey Wolf Optimization with Cuckoo Search Algorithm for load frequency controller design of hybrid power system - Khadanga, Rajendra Kumar; Kumar, Amit; Panda, Sidhartha (Applied soft computing, 2022)
This paper proposes a novel strategy by consolidating the Modified Grey wolf optimization algorithm and the Cuckoo search algorithm, termed as MGWO-CS algorithm. The superiority of the proposed modified hybrid algorithm over the original algorithm in terms of implementation time and solution quality is compared by taking several benchmark test functions. Further, the genuine utilization of the proposed algorithm is tried by designing a TID controller for frequency regulation of a two-area power system with the application of a photovoltaic system. The matchless quality of the MGWO-CS based TID controller is presented by contrasting with some current methods. Finally, the robustness of the hybrid algorithm-based controller is tested in a multi-area multi-source hybrid power system with the PV-Thermal environment and it is observed that the proposed hybrid algorithm based TID controller is more effective for the load frequency control of the hybrid system compared to the conventional controller. •A novel Modified Grey Wolf Optimization Integrated with Cuckoo Search Algorithm is proposed.•The superiority of hybrid algorithm over some conventional techniques is compared by taking several benchmark test functions.•Further, the algorithm is employed for design of a TID Controller for load frequency controller of a two-area power system.•The Two-Area power system includes the renewable sources like solar and thermal generator.•Finally, the proposed method is tested in a multi-area multi-source system by considering the actual scenarios of the system.